A broad spectrum anti-HIV inhibitor significantly disturbs V1/V2 domain rearrangements of HIV-1 gp120 and inhibits virus entry. (3rd March 2016) - Berinyuy, Emiliene; Soliman, Mahmoud E. S.
Abstract: Inhibition of human immunodeficiency virus (HIV) entry into target human cells is considered as a critical strategy for preventing HIV infection. Conformational shifts of the HIV-1 envelope glycoprotein (gp120) facilitates the attachment of the virus to target cells, therefore gp120 remains an attractive target for antiretroviral therapy development. Compound18A has been recently identified as a broad-spectrum anti-HIV inhibitor. It was proposed that18A disrupts rearrangements of V1/V2 region in gp120; however, the precise mechanism by which18A interferes with the inherent motion of V1/V2 domain remains obscure. In this report, we elaborate on the binding mode of compound18A to the closed conformation of a soluble cleaved gp120 and further examine the dynamic motion of V1/V2 region in both gp120 and the gp120–18A complex via all-atom molecular dynamics simulations. In this work, comparative molecular dynamic analyses revealed that18A makes contact with Leu179, Ile194, Ile424, Met426 W427, E370 and Met475 in the main hydrophobic cavity of the unliganded gp120 and disrupts the restructuring of V1/V2 domain observed in apo gp120. The unwinding of α1 and slight inversion of β2 in gp120 leads to the shift of VI/V2 domain away from the V3 N-terminal regions and toward the outer domain. Stronger contacts between Trp425 and Trp112 rings may contribute to the reduced flexibility of α1 observed upon18A binding thereby inhibiting the shifts of the V1/V2 region. Binding of18A to gp120: (1) decreases the overall flexibility of the protein and (2) inhibits the formation a gp120 conformation that closely ressembles a CD4-bound-like conformation. Information gained from this report not only elaborates on important dynamic features of gp120, but will also assist with the future designs of potent gp120 inhibitors as anti-HIV.